Risks in Housing and Real Estate Construction Project - Koirala, Madhav Prasad (Journal of the Institute of Engineering, 2014)
The main purpose of this paper is identify the risks involved in housing and real estate of construction projects in Nepal and ranks them as per the severity. In this research, first the risks involved in construction projects life cycle has been identified with the help of professional expertise and verified with the help of housing profession arranged in a respondent in systematic hierarchical structure. Questionnaire surveys and literature review were used for data collection. Next, based on the obtained data a network was based on the statically system has been designed for the evaluation of project risks. After data analysis, the result has been published and finally conclusion has been drawn. DOI: http://dx.doi.org/10.3126/jie.v10i1.10876 Journal of the Institute of Engineering, Vol. 10, No. 1, 2014 pp. 34-44